(untitled) (Bangladesh Journal of Urology, 2020)
Background: Renal stone disease is a common disorder with a prevalence ranging from 4-15% in different parts of the world. Modalities of kidney stone management includes drug therapy, extracorporeal shock wave lithotripsy (ESWL), percutaneous nephrolithotomy (PCNL), Retrograde intrarenal surgery ureteroscopy (RIRS) and open surgery. ESWL is an acceptable technique and widely used because it is a non-invasive treatment and does not require anesthesia and usually done on an outpatient basis. Generally, ESWL is the treatment of choice for kidney stones <1 cm. However, not all ESWL treatments are successful. The success rate has been reported to be between 50%-87%, depending on various factors. This study was conducted in order to evaluate thefactors affecting renal stones treatment by extracorporeal shock wave lithotripsy (ESWL).On the basis of different variables andfactors affecting the renal stones treatment by ESWL was evaluated. Objectives: To evaluate the factors affecting the outcome of Extracorporeal Shock Wave Lithotripsy (ESWL) in the treatment of renal stone in adults.To assess the success and failure rate by using ESWL for treatment of renal stone, to determine the effects of stone related factors to correlate the success rate with characteristics of the patients condition of the urinary tract and stone features; to observe the patient groups most likely to benefit from or fail an initial intervention with ESWL and to evaluate the post ESWL complications. Materials and methods: This is a prospective observational and analytical, hospital based study. Total 500 patients with single or multiple radio-opaque renal stones were treated with ESWL monotherapy using Siemens MODULARIS Variostarlithotriptor. This study was carried out inthe Department of Urology, Combined Military Hospital, Dhaka for a period of two years between 01 July 2015 to 31 July 2017. The results of treatment were evaluated after 3 months of follow-up. Treatment success was defined as complete clearance of the stones or presence of clinically insignificant residual fragments (<3mm). The results of treatment were correlated with the patient characteristics (age, sex, body mass index) and stone features (size, site, number & radio density). Results: At 3-months follow-up, the overall success rate is 87.6%. Among them, repeated ESWL sessions were required in 266 patients (53.2%). Post-ESWL complications were recorded in 62 patients (12.4%). Using the chi-square test, only four factors have a significant impact on the success rate, namely stone site, size (the largest diameter of the stone), stone number, BMI (body mass index) of the patient. The success rate is highest for stones located in the upper calyx (136/136; 100%) and lowest for those located in lower calyx 104/78; 75%) (p=0.001). Stone with a largest diameter of <10mm are associated with a success rate of 93.6% (307/328), compared to 76.2% (131/172) for those with a diameter of >10mm (p=0.001). The success rate was also higher for single stone (396/437; 90.6%) than multiple stones (42/63; 66.7%) (p=.001). Patients with lower BMI (<24) have a better success than higher BMI (>25) (p=.001). Other factors including age, sex and stone radio density compared to ipsilateral 12th rib have no significant impact on the success rate. Conclusion: The success rate of ESWL for the treatment of renal stones can be predicted by stone size, location, number, and patients BMI. Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.141-150